2018
DOI: 10.29312/remexca.v9i3.1218
|View full text |Cite
|
Sign up to set email alerts
|

Concentraciones e intervalos de aplicación del aceite esencial de Tagetes lucida Cav. contra Nacobbus aberrans

Abstract: La escaza información sobre los efectos del aceite esencial de Tagetes lucida contra nematodos y la riqueza de poblaciones nativas de esta especie vegetal en algunas áreas en el Estado de México resultan condiciones favorables para derivar insumos naturales inocuos de esta especie que posibiliten enfrentar problemas de agallamiento por N. aberrans en la producción de jitomate. El objetivo de este estudio fue evaluar en condiciones de invernadero la aplicación de aceite de T. lucida de una … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Nevertheless, a different quantitative and qualitative composition has also been documented in plants collected from Mexico [15], in which the main compound was geranyl acetate (49.9%). A perusal of the literature reveals at least four different chemotypes of T. lucida based on essential oil composition: (1) an estragole-dominated chemotype [10][11][12][13][14], (2) an estragol/anethol chemotype [15,16], (3) a methyl eugenol chemotype [17], and (4) a geranyl acetate-rich chemotype [17,18]. The phenylpropanoid estragole is found in numerous EOs and is known to possess different pharmacological properties, such as antifungal [19], antiparasitic [20,21], and anti-inflammatory [22] activity.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, a different quantitative and qualitative composition has also been documented in plants collected from Mexico [15], in which the main compound was geranyl acetate (49.9%). A perusal of the literature reveals at least four different chemotypes of T. lucida based on essential oil composition: (1) an estragole-dominated chemotype [10][11][12][13][14], (2) an estragol/anethol chemotype [15,16], (3) a methyl eugenol chemotype [17], and (4) a geranyl acetate-rich chemotype [17,18]. The phenylpropanoid estragole is found in numerous EOs and is known to possess different pharmacological properties, such as antifungal [19], antiparasitic [20,21], and anti-inflammatory [22] activity.…”
Section: Resultsmentioning
confidence: 99%
“…by this nematode when applied at 10 mg/ml of essential oil (Zarate-Escobedo et al, 2018). These previous studies could help explain the anthelmintic effect found using this plant.…”
Section: Discussionmentioning
confidence: 56%
“…at concentrations of 0.35 and 10 mg mL −1 produced 47% to 95% galling inhibition of N. aberrans with LC 50 values of 0.06 to 0.13 mg mL −1 in application intervals of 2 and 3 weeks, respectively. The activity of the essential oil was attributed to the presence of geranyl acetate, β ‐ocimene, nerolidol, β ‐cubebene, and caryophyllene …”
Section: Discussionmentioning
confidence: 99%
“…The activity of the essential oil was attributed to the presence of geranyl acetate, -ocimene, nerolidol, -cubebene, and caryophyllene. 46 Several chromatographic and spectral analytical techniques, including UV-Vis spectroscopy, gas chromatography/ion trap mass spectrometry (GC/ITMS), HPLC coupled with photodiode array detection and electrospray ionization-mass spectrometry (LC/PDA/ESI-MS), have been used for separation, characterization, and qualitative and quantitative determination of the lipidic, phenolic, and volatile fraction from H. inuloides. 37,[47][48][49][50][51] Due to the nature of the metabolites present in the flowers of H. inuloides, maceration with acetone allows the extraction of bioactive compounds with different polarities.…”
Section: Discussionmentioning
confidence: 99%